2024
DOI: 10.1007/s12035-024-04059-x
|View full text |Cite
|
Sign up to set email alerts
|

The Long Non-Coding RNA NR3C2-8:1 Promotes p53-Mediated Apoptosis through the miR-129-5p/USP10 Axis in Amyotrophic Lateral Sclerosis

Dejiang Pang,
Yujiao Yu,
Bi Zhao
et al.

Abstract: Motor neuron degeneration in amyotrophic lateral sclerosis (ALS) is a form of apoptosis, but the mechanisms underlying this neuronal cell death remain unclear. Numerous studies demonstrate abnormally elevated and active p53 in the central nervous system of ALS patients. Activation of p53-regulated pro-apoptotic signaling pathways may trigger motor neuron death. We previously reported decreased expression of the long non-coding RNA NR3C2-8:1 (Lnc-NR3C) in leukocytes of ALS patients. Here, we show lnc-NR3C promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…Recent studies have shown that SERPINA1 [563], LRRK2 [522], CHRNA4 [564], CD22 [565], TF (transferrin) ssociated tyrosine kinase) [579], FGF14 [580], INSC (INSC spindle orientation adaptor protein) [581], BARHL1 [582], PRKCH (protein kinase C eta) [583], SLC24A4 [584], TMEM176B [585], MBP (myelin basic protein) [586], ACAN (aggrecan) [587], SHH (sonic hedgehog signaling molecule) [588], SIRT2 [589], RBP4 [590], ISM1 [591], HOXB6 [592], CDH13 [593], NTF3 [594], TRPC6 [595], MMP3 [596], HLA-DRB5 [597], HLA-DRB1 [546], CD74 [598], VWF (von Willebrand factor) [599], MDGA1 [600], ANGPT2 [601], NEDD4L [602], CASP1 [603], CHRNA5 [604], CCND2 [605], BRCA2 [606], TET1 [607], ZBTB20 [608], OAS1 [609], EGFR (epidermal growth factor receptor) [610], ABCA1 [611], PLXNA4 [612], FOXG1 [613], WEE1 [433], MAP1B [614], ANK1 [615], GRM3 [436], COMT (catechol-O-methyltransferase) [616], SLC10A4 [617], GPR39 [618] and LIFR (LIF receptor subunit alpha) [562] could promote Alzheimer’s disease progression. SERPINA1 [619], LRRK2 [620], CHRNA4 [621], TLR2 [622], MOBP (myelin associated oligodendrocyte basic protein) [623], AATK (apoptosis associated tyrosine kinase) [624], MBP (myelin basic protein) [625], SHH (sonic hedgehog signaling molecule) [626], XDH (xanthine dehydrogenase) [627], RBP4 [628], GRIA2 [629], NR3C2 [630], HLA-DRB5 [631], HLA-DRA [631], NEDD4L [632], CASP1 [633], EFNB2 [634], CYP7B1 [635], EGFR (epidermal growth factor receptor) [636], MAP1B [637], GRM3 [638<...…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that SERPINA1 [563], LRRK2 [522], CHRNA4 [564], CD22 [565], TF (transferrin) ssociated tyrosine kinase) [579], FGF14 [580], INSC (INSC spindle orientation adaptor protein) [581], BARHL1 [582], PRKCH (protein kinase C eta) [583], SLC24A4 [584], TMEM176B [585], MBP (myelin basic protein) [586], ACAN (aggrecan) [587], SHH (sonic hedgehog signaling molecule) [588], SIRT2 [589], RBP4 [590], ISM1 [591], HOXB6 [592], CDH13 [593], NTF3 [594], TRPC6 [595], MMP3 [596], HLA-DRB5 [597], HLA-DRB1 [546], CD74 [598], VWF (von Willebrand factor) [599], MDGA1 [600], ANGPT2 [601], NEDD4L [602], CASP1 [603], CHRNA5 [604], CCND2 [605], BRCA2 [606], TET1 [607], ZBTB20 [608], OAS1 [609], EGFR (epidermal growth factor receptor) [610], ABCA1 [611], PLXNA4 [612], FOXG1 [613], WEE1 [433], MAP1B [614], ANK1 [615], GRM3 [436], COMT (catechol-O-methyltransferase) [616], SLC10A4 [617], GPR39 [618] and LIFR (LIF receptor subunit alpha) [562] could promote Alzheimer’s disease progression. SERPINA1 [619], LRRK2 [620], CHRNA4 [621], TLR2 [622], MOBP (myelin associated oligodendrocyte basic protein) [623], AATK (apoptosis associated tyrosine kinase) [624], MBP (myelin basic protein) [625], SHH (sonic hedgehog signaling molecule) [626], XDH (xanthine dehydrogenase) [627], RBP4 [628], GRIA2 [629], NR3C2 [630], HLA-DRB5 [631], HLA-DRA [631], NEDD4L [632], CASP1 [633], EFNB2 [634], CYP7B1 [635], EGFR (epidermal growth factor receptor) [636], MAP1B [637], GRM3 [638<...…”
Section: Discussionmentioning
confidence: 99%